Helicobacter pylori and its secreted immunomodulator VacA protect against anaphylaxis in experimental models of food allergy. Issue 10 (11th September 2017) - Kyburz, A.; Urban, S.; Altobelli, A.; Floess, S.; Huehn, J.; Cover, T. L.; Müller, A.
Summary: Background: Food allergy is an increasingly common health problem in Western populations. Epidemiological studies have suggested both positive and negative associations between food allergy and infection with the gastric bacterium Helicobacter pylori . Objective: The objective of this work was to investigate whether experimental infection with H. pylori, or prophylactic treatment with H. pylori ‐derived immunomodulatory molecules, affects the onset and severity of food allergy, either positively or negatively. Methods: We infected neonatal C57BL/6 or C3H mice with H. pylori or treated animals with H. pylori components (bacterial lysate or the immunomodulator VacA) and subsequently subjected them to four different protocols for food allergy induction, using either ovalbumin or peanut extract as allergens for sensitization and challenge. Readouts included anaphylaxis scoring, quantification of allergen‐specific serum IgE and IgG1 and of the mast cell protease MCPT1, as well as splenic T‐helper‐2 cell‐derived cytokine production. Mesenteric lymph node CD4 + FoxP3 + regulatory T cells were subjected to flow cytometric quantification and sorting followed by qRT‐PCR, and to DNA methylation analyses of the Treg‐specific demethylated region (TSDR) within the FOXP3 locus. Results: Mice that had been infected with H. pylori or treated with H. pylori ‐derived immunomodulators showed reduced anaphylaxis upon allergen sensitization and challenge, irrespective of the allergen used. Most of the immunologic assays confirmed a protective effect of H. pylori . CD4 + FoxP3 + T cells were more abundant in protected mice and exhibited a stable Treg phenotype characterized by FOXP3 TSDR demethylation. Conclusions and Clinical Relevance: Helicobacter pylori confers protection against the anaphylaxis associated with ovalbumin and peanut allergy and affects the epigenome of T cells, thereby promoting stable Treg differentiation and functionality. Prophylactic treatment with H. pylori ‐derived immunomodulators appears to be a promising strategy for food allergy prevention.